Pluripotent Stem Cell-Based Drug Screening Reveals Cardiac Glycosides as Modulators of Myotonic Dystrophy Type 1 - Maury, Yves; Poydenot, Pauline; Brinon, Benjamin; Lesueur, Lea; Gide, Jacqueline; Roquevière, Sylvain; Côme, Julien; Polvèche, Hélène; Auboeuf, Didier; Alexandre Denis, Jérome; Pietu, Geneviève; Furling, Denis; et al. (iScience, 2019)
There is currently no treatment for myotonic dystrophy type 1 (DM1), the most frequent myopathy of genetic origin. This progressive neuromuscular disease is caused by nuclear-retained RNAs containing expanded CUG repeats. These toxic RNAs alter the activities of RNA splicing factors, resulting in alternative splicing misregulation. By combining human mutated pluripotent stem cells and phenotypic drug screening, we revealed that cardiac glycosides act as modulators for both upstream nuclear aggregations of DMPK mRNAs and several downstream alternative mRNA splicing defects. However, these occurred at different drug concentration ranges. Similar biological effects were recorded in a DM1 mouse model. At the mechanistic level, we demonstrated that this effect was calcium dependent and was synergic with inhibition of the ERK pathway. These results further underscore the value of stem-cell-based assays for drug discovery in monogenic diseases. [Display omitted] •Myotonic dystrophy type 1 hPSCs were adapted for high content screening•FDA-approved cardiac glycosides normalize in vitro and in vivo DM1 biological markers•Cardiac glycosides synergize with the ERK pathway to normalize DM1 biomarkers•This study emphasizes the value of human pluripotent stem cells for drug discovery Physiology; Molecular Biology; Cell Biology